2021
DOI: 10.1021/acsnano.1c05212
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Chiral Supramolecular Microenvironment Strategy for Enhanced Biocatalysis

Abstract: How the three-dimensional (3D) chiral environment affects the biocatalysis remains an important issue, thereby inspiring the development of a microenvironment that highly mimics the natural features of enzyme to guarantee enhanced biocatalysis. In this study, two gelators bearing d/l-phenylalanine as chiral centers are designed to construct the 3D chiral catalytic microenvironment for enhancing the biocatalysis of lipase. Such a microenvironment is programmed through chiral transmission of chirality from molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…During the freezing of PVA–SA solution, ice formed in the amorphous region induced the growth of PVA polymer crystallites, which act as nodule points of the network and promote the formation of hydrophobic fibers. 33 The produced PVA–SA fibers were uniform without any beads but showed minor defects (Fig. 1A).…”
Section: Resultsmentioning
confidence: 93%
“…During the freezing of PVA–SA solution, ice formed in the amorphous region induced the growth of PVA polymer crystallites, which act as nodule points of the network and promote the formation of hydrophobic fibers. 33 The produced PVA–SA fibers were uniform without any beads but showed minor defects (Fig. 1A).…”
Section: Resultsmentioning
confidence: 93%
“…These high‐aspect‐ratio nanofibers template through hydrogen bonding along the long axis of nanofibers and further physically entangle to self‐supportive 3D hydrogels networks by a supramolecular gelation process (Scheme 1A). [ 18 ] The critical gel concentration (CGC) for L ‐BA, D ‐BA, and R ‐BA is 1.0 wt.%, and hydrogel formation was judged by the conventional tube inversion method (Figure S7 and Table S1, Supporting Information). The water content of these three hydrogels was measured by the method of drying and weighing was almost above 98% (Figure S8A, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The M ‐type and P ‐type hydrogels showed the absorptive dissymmetry factor g abs , which is defined by the ratio of CD intensity to the corresponding absorption (shown in Supporting Information), were approximately equal in intensity and handedness opposite in chirality (Figure 1F), which indicated that the molecular chirality of the gelators is well transferred to the supramolecular chirality. [ 14,18 ] With the increasing testing temperature, the intensity of the CD signals for both M ‐type and P ‐type self‐assembling hydrogels gradually decreased due to disassembly by heating. At ≈95 °C, the CD signals at 230 and 306 nm both almost disappeared suggesting the disintegration of M ‐type and P ‐type self‐assembled nanofibers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…During freezing of the solution, the ice created in the amorphous region induced the growth of polymer crystallites, acting as junction knots of the network and enhancing mechanical strength of hydrogel. [ 39 ] CD spectra were measured and compared to investigate the interactions of the hydrogels (Figure 1i). CFPL hydrogel (CS + PVA + LBF) showed negative peaks at ≈227 and 256 nm and positive CD absorptions at ≈206 and 288 nm, while the mirror‐imaged CD spectrum of CFPD hydrogel (CS + PVA + DBF) exhibited three positive bands (204, 226, and 260 nm) and two negative bands (≈208 and 288 nm).…”
Section: Resultsmentioning
confidence: 99%